2009
DOI: 10.1016/j.jcrysgro.2009.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of (111)-oriented Si layers on SiO2 substrates by an aluminum-induced crystallization method and subsequent growth of semiconducting BaSi2 layers for photovoltaic application

Abstract: a b s t r a c tWe have prepared (111)-oriented Si layers on SiO 2 (fused silica) substrates from amorphous-Si(a-Si)/Al or Al/a-Si stacked layers using an aluminum-induced crystallization (AIC) method. The X-ray diffraction (XRD) intensity from the (111) planes of Si was found to depend significantly on growth conditions such as the thicknesses of Si and Al, deposition order (a-Si/Al or Al/a-Si on SiO 2 ), deposition technique (sputtering or vacuum evaporation) and exposure time of the Al layer to air before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…In the case of Si, isothermal annealing of amorphous Si (a-Si)/Al layers on glass at temperatures below the eutectic temperature (577 1 C) results in layer exchange and formation of a continuous polycrystalline Si thin film [2][3][4][5].The preferential growth orientation is known to be either /1 0 0S or /1 1 1S depending on growth conditions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Si, isothermal annealing of amorphous Si (a-Si)/Al layers on glass at temperatures below the eutectic temperature (577 1 C) results in layer exchange and formation of a continuous polycrystalline Si thin film [2][3][4][5].The preferential growth orientation is known to be either /1 0 0S or /1 1 1S depending on growth conditions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrate a straightforward, highly scalable process for the growth of large grain, c‐axis textured GaN films that is applicable to a variety of amorphous and polycrystalline substrates. The process employs a thin (≈30 nm) Si (111) template layer with grain sizes of 30–40 μm formed by aluminum‐induced crystallization (AIC) of amorphous Si at 400–500 °C. These layers are formed on fused quartz, thermally oxidized Si (001), and polycrystalline diamond substrates.…”
mentioning
confidence: 99%
“…The quality of the Al 2 O 3 can also be influenced by the Al deposition process. For example, Tsukada et al suggested that sputter deposition of Al leads to a rough surface which, in turn, reduces the thickness uniformity of the Al 2 O 3 layer . The Al 2 O 3 /Al layer is then coated with an a‐Si layer with a thickness equal to or less than thickness of the Al layer to ensure that a smooth poly‐Si layer is produced.…”
Section: Introductionmentioning
confidence: 99%